2006
DOI: 10.1161/01.str.0000206281.77178.ac
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Potentiate Damage to Blood–Brain Barrier Constituents

Abstract: Background-Blood-brain barrier (BBB) disruption after stroke can worsen ischemic injury by increasing edema and causing hemorrhage. We determined the effect of microglia on the BBB and its primary constituents, endothelial cells (ECs) and astrocytes, after ischemia using in vivo and in vitro models. Methods and Results-Primary astrocytes, ECs, or cocultures were prepared with or without added microglia. Primary ECs were more resistant to oxygen-glucose deprivation/reperfusion than astrocytes. ECs plus astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
272
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 335 publications
(287 citation statements)
references
References 45 publications
12
272
1
2
Order By: Relevance
“…24 It was reported that microglia could exacerbate endothelial cell death after oxygen and glucose deprivation and that treatment with minocycline, a drug known to reduce microglial activation and proliferation, 8 could attenuate this phenomenon. 25 Recombinant tPA induces a catalyticindependent activation of the extracellular signal-regulated kinase 1/2 and Jun N-terminal kinase leading to microglial activation in culture. 21 Thus, preventing rtPA-related enhancement of microglial cell recruitment and activation after stroke could possibly limit ischemic brain infarction.…”
Section: Discussionmentioning
confidence: 99%
“…24 It was reported that microglia could exacerbate endothelial cell death after oxygen and glucose deprivation and that treatment with minocycline, a drug known to reduce microglial activation and proliferation, 8 could attenuate this phenomenon. 25 Recombinant tPA induces a catalyticindependent activation of the extracellular signal-regulated kinase 1/2 and Jun N-terminal kinase leading to microglial activation in culture. 21 Thus, preventing rtPA-related enhancement of microglial cell recruitment and activation after stroke could possibly limit ischemic brain infarction.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Recent work has shown that microglia can potentiate injury to blood-brain barrier constituents (astrocytes and endothelial cells) via NOX-mediated superoxide in cell culture models of ischemia. 13 In addition, several groups have shown that mice deficient in the gp91 subunit of NOX2 have smaller infarcts than do wild-type mice, [27][28][29] and that outcomes from experimental cerebral ischemiareperfusion are improved with early administration of the pharmacological NOX inhibitors apocynin 29 -33 and honokiol. 34,35 These results identify NOX as a promising target for therapeutic intervention, but it is possible that the efficacy of these treatment strategies may be due largely or in part to inhibition of NOX in cell types other than microglia.…”
Section: Superoxide Productionmentioning
confidence: 99%
“…It is important, however, to place this approach in context. Although there is now strong evidence that the inflammatory response can exacerbate ischemic injury, [13][14][15][16][17][18] there is also evidence that some aspects of the inflammatory response are important for tissue repair. These aspects include phagocytosis of cell debris, remodeling of the extracellular matrix, and the release of cytokines and trophic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, it is the inflammation (phagocytosis) that leads to the restoration of tissue structure and function [96,97]. Although inflammation is triggered primarily to remove the blood and other debris left by the hemorrhage, the byproducts of this response are cytotoxic and lead to further tissue damage, blood brain barrier disruption, and edema [72,97,98].…”
Section: Pharmacologic Hematoma Clearancementioning
confidence: 99%
“…Other Treatment Modalities Additional treatments that are being evaluated for ICH treatment include hypothermia [148,149], stem cells, minocycline [98,150], and rehabilitation interventions [151][152][153]. The latter treatment modalities are currently in the early stages of preclinical development.…”
Section: Management Of Ich In Patients On Concurrent Antithrombotic Tmentioning
confidence: 99%